The use of television by blacks in the PWV area - S. J. Bekker (Communicare)
This article focuses on Rayburn and Palmgreen's (1984) expectancy-value model of gratifications to determine the way in which members of a group of blacks utilize television as a mass medium to satisfy certain needs through selective exposure to their favourite programmes. Also, an attempt is made to test the basic assumptions of the model. The sample consisted of 703 urban blacks in the PWV area, and was divided into four groups, viz. a satisfied, unrealistic, surprised, and passive group for each of news, educational, and story programmes. The results indicate that the majority of the respondents are satisfied with these television programmes of the SABC. It appears as if the model, which was tested for the whole sample regarding various programmes, should be adapted to enhance its applicability for intercultural studies and the use of television in general